Parents' Perception of Islamic Religious Education and Its Impact on Child Psychology: A Case Study in SD Negeri 1 Perian - Muhibbin Muhibbin; Abdul Munib (Kuttab: Jurnal Ilmu Pendidikan Islam, 2026)
This study aims to explore parents’ perceptions of religious education and its impact on children’s psychology. The research employs a qualitative case-study design. Data collection techniques included interviews, observations, and documentation. The data analysis process involved interview transcription. The findings indicate that some parents perceive IRE as playing a highly significant role in life because it provides direction and guidance. However, several factors may influence the implementation of IRE for children, as expressed by parents, including educational background, economic conditions, environment, and peer associations. Furthermore, regarding the impact of IRE on children’s psychology, parents believe that religious education significantly affects not only individual life but also family life, neighbourhood relations, and civic life in general.